GE_GERICHTE P/2410/2018 vom 22. Mai 2019 - GE Cour de justice (2019)
DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL) ; VIOLATION DE DOMICILE ; PLAINTE PÉNALE ; ASSOCIATION ; PERSONNE MORALE | CP.30; CP.144.al1; CP.144.al3; CP.186